Effect of Service Quality, Price, and Location on Customer Loyalty: A Pandemic-Era Barbershop Study: Pengaruh Kualitas Pelayanan, Harga, dan Lokasi terhadap Loyalitas Pelanggan: Studi Barbershop Era Pandemi - Ahmad Rizki Zamnur; Slamet Harjatno (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of service quality, price, and location on customer loyalty, with customer satisfaction as the mediating variable, in the context of a barbershop during the COVID-19 pandemic. Using a quantitative approach, data from 100 respondents who visited Elcapitano barbershop in Sidoarjo were collected through purposive nonprobability sampling. The research employs path analysis via Smart PLS 3.0. The findings reveal that service quality significantly influences customer loyalty, while price has no significant effect on loyalty, and location also does not impact loyalty. Furthermore, service quality positively affects customer satisfaction, price affects customer satisfaction, and location influences customer satisfaction. Lastly, customer satisfaction is shown to have a significant influence on customer loyalty. Specifically, service quality influences customer loyalty through customer satisfaction, whereas price does not affect loyalty through satisfaction, and location affects loyalty through customer satisfaction. These findings offer valuable insights for barbershop owners and similar businesses in enhancing customer loyalty during challenging times, such as a pandemic. Highlights: Mediating Role of Customer Satisfaction: This study underscores the crucial role of customer satisfaction as a mediator in the relationship between service quality, price, location, and customer loyalty. It highlights how a satisfied customer base is essential for building loyalty. Impact of Service Quality: The research emphasizes the significant influence of service quality on customer loyalty, underscoring the importance of providing high-quality services to retain and attract loyal customers. Resilience in Challenging Times: This study's relevance extends to businesses facing challenges like the COVID-19 pandemic, as it provides insights into strategies for maintaining and strengthening customer loyalty even during such difficult periods. Keywords: service quality, price, location, customer loyalty, customer satisfaction